Performance of selenate removal by biochar embedded nano zero-valent iron and the biological toxicity to Escherichia coli. Issue 45 (21st August 2019) - Liang, Liping; Xue, Yuanyuan; Tian, Gangliang; Mao, Qiaole; Lou, Zixuan; Wu, Qian; Wang, Qian; Du, Juanshan; Meng, Xu
Abstract : The application of nano zero-valent iron (nZVI) in water environment was limited by its easily aggregation and potential biological toxicity. Abstract : The application of nano zero-valent iron (nZVI) in water environment was limited by its easily aggregation and potential biological toxicity. In this study, biochar embedded nZVI (BC-nZVI) was prepared by carbon-thermal reduction method, and the SEM-EDX mapping results showed that nZVI was successfully embedded on biochar. Meanwhile, BC-nZVI with the optimal Fe/C of 2/1 showed a similar Se(vi ) removal efficiency to pure nZVI. Effects of pH, BC-nZVI loading, and initial Se(vi ) concentration were studied. Se(vi ) removal rates (at 30 min) by BC-nZVI at pH 4.0 and 5.0 were 98.2% and 95.9%, respectively. But Se(vi ) removal rate (at 30 min) was sharply decreased to 25.8% at pH 6.0. With the increase of BC-nZVI loading from 0.5 g L −1 to 1 g L −1, Se(vi ) removal rate (at 30 min) significantly increased from 25.5% to 95.9%. And the continuous increase of BC-nZVI loading to 2 g L −1 did not improve Se(vi ) removal rate. Se(vi ) less than 3 mg L −1 was completely removed by BC-nZVI in 30 min, but Se(vi ) more than 6 mg L −1 only was removed about 25.9% at 30 min. Optimal parameters were pH 4.0, 2 g L −1 BC-nZVI, and 1.5 mg L −1 Se(vi ). Variation of calculated amount, SOD activity, and protein content of Escherichia coli with nZVI and BC-nZVI indicated that nZVI and BC-nZVI both produced negative effects on the growth of E. coli . But the amount and SOD activity of E. coli with pure nZVI was lower than that with BC-nZVI. Moreover, E. coli with nZVI released more protein than that with BC-nZVI. So modified nZVI by biochar was less harmful to E. coli than nZVI.